THE AMUR RIVER WATER DURING THE WINTER LOW WATER PERIOD: THE MANY-YEAR DYNAMICS OF THE SULFATES CONTENT AND RUNOFF - Vladimir P. Shesterkin; Nina M. Shesterkina (Водное хозяйство России: проблемы, технологии, управление)
Sulfates are the dominant ions among the major ones in the Amur region’s sewage. Therefore, the purpose of the research is to study the long-term dynamics of the content and runoff of sulfates in the Amur River in the winter low-water, based on the materials of Roshydromet for 1943-1976 and the author’s data for 1999-2019.Significant variations in the main areas were found due to both the diversity of natural conditions and anthropogenic influence in the areas of large cities and localities. The impact of the construction of hydroelectric power plants, significant economic changes in the Chinese part of the Amur basin, as well as the closure of pulp and paper and microbiological industries in the Russian part of the Amur basin on the long-term dynamics of the content and flow of sulfates is estimated. The maximum content of sulfates in the Amur River was observed after the accident at the Jilin chemical plant in China in December 2005. The influence of major floods on the increase in the flow of sulphates in the winter low-water was established.